Early Stages and Biology of Melitaea timandra Coutsis et Oorschot, 2014(Lepidoptera, Nymphalidae) Under the Conditions of Kuh-e-Binalud Mountain (Iran) - Kolesnichenko, Kirill A.; Kotlobay, Anatoly A. (Zootaxa, 2020)
This article presents characteristics of the habitats and flying period of Melitaea timandra Coutsis et Oorschot, 2014 and describes the behavior of the adults under natural conditions, their food plant, egg chorion morphology, and caterpillars of the first and senior instars. In addition, a larval parasitoid is identified as Cotesia sp., and the possible development cycle of M. timandra is described.